Comment les corps techniques construisent la ville - Benedikte Zitouni; Céline Tellier (Brussels Studies, 2013)
This article combines the results of two doctoral research papers and is the fruit of work carried out within the framework of a more global study on the elite in the city. Two sociologists relate the plans for the extension of the city by the road inspectorate in the 19th century and the creation of the underground by the Service Spécial d’Etudes of the STIB in the 20th century. Behind the scenes in the state departments, by dissecting the internal archives of the administration (correspondence, reports, notes and circulars), we discover that civil servants and, more specifically, the technical bodies have developed a practice of time allowing the step-by-step realisation of large-scale projects. Time is a tactical and flexible element in these cases, formulated and manipulated in order to prompt an expansion of the city and to ensure the irreversible commitment of the stakeholders involved. The conclusion shared by the two analyses carried out in parallel questions the idea that it is necessary to have powerful visions and authority for Brussels in order to face major urbanistic challenges. As an alternative, based on information from the history of organisations, the authors propose to examine the technical bodies and their knowledge and capacity to act as mediators.